Social Media Fatigue Ditinjau dari Stres Akademik selama Pembelajaran Daring di Masa Pandemi COVID-19 - Amalia Nurhalizah; Fitriana Widyastuti (Jurnal Psikologi Integratif, 2023)
The online learning during the Covid-19 pandemic forces students to be continuously exposed to the use of social media which triggers social media fatigue. This study aims to determine the relationship between academic stress and social media fatigue during online learning during the Covid-19 pandemic. This study involved 100 respondents who were taken by accidental sampling technique. Research respondents are students who take full online learning. The research instruments used were the Social Media Fatigue Scale and the Student Life Stress Inventory. The results showed that there was positive relationship between academic stress and social media fatigue, with an effective contribution of 22.4%. Implications of the results of this study refer to the need for modifications in the learning process to reduce learning pressure and social media fatigue. Proses pembelajaran daring selama pandemic Covid-19 memaksa pembelajar untuk secara terus-menerus terpapar dengan penggunaan media social yang memicu social media fatigue. Penelitian ini bertujuan untuk mengetahui hubungan antara stress akademik dengan social media fatigue selama pembelajaran daring selama pandemic Covid-19. Penelitian ini melibatkan 100 responden penelitian yang diambil dengan teknik accidental sampling. Responden penelitian merupakan mahasiswa yang mengikuti pembelajaran daring secara penuh. Instrumen penelitian yang digunakan adalah Skala Social Media Fatigue dan Student Life Stress Inventory. Hasil penelitian menunjukkan bahwa terdapat hubungan positif antaran stress akademik dan social media fatigue, dengan sumbangan efektif sebesar 22,4%. Implikasi hasil penelitian ini merujuk pada perlunya modifikasi dalam proses pembelajaran untuk mengurangi tekanan dalam belajar dan social media fatigue.